Process development for higher yield production of diacylglycerol oil via partial hydrolysis - Phuah, Eng Tong (2015)
The disclosure of diacylglycerol (DAG) oil to replace the conventional edible oils has received increasing interest among researchers and food manufacturers owing to its anti-obesity properties. Distinct processing approaches have been proposed to produce DAG-enriched oil in which enzymatic partial hydrolysis outstands other methods due to its inexpensive raw materials and single-step hydrolytic reaction involved. In present work, single-factor optimization of partial hydrolysis for DAG production from refined, bleached, deodorized palm oil (RBDPO) catalysed by immobilized Rhizomucor miehei lipase (Lipozyme RMIM) was carried out in batch system. Effects of four operating parameters namely temperature, enzyme dosage, water content and agitation speed were investigated. Optimum production conditions for palm based-DAG are as follows: temperature = 55oC, enzyme dosage = 10-wt%, water content = 5-wt% and agitation speed = 500 rpm. A DAG yield of 31-wt% was obtained after 6 h of reaction. The partial hydrolysis reaction was found to conform to Ping-Pong Bi-Bi with substrate inhibition mechanism. The optimum operating conditions were then applied to the lab-scale packed bed system. Packed bed reactor (PBR) is an effective reactor configuration because it enables reusability of the enzyme particles besides enhancing its operational stability. However, mass transfer limitation remains a key challenge in packed bed column system, especially at large scale. A dimensionless mathematical mass transfer model of Colburn factor, JD, which is a function of Reynolds (Re) and Schmidt (Sc) numbers, was therefore developed to simulate mass transfer phenomena of the reaction mixture in PBR during enzymatic partial hydrolysis reaction. The results revealed that the mass transfer correlation of JD=0.92(Re)- 0.2 was able to predict the experimental data accurately. In addition, response surface methodology (RSM) was employed to optimize the process variables namely packed bed height and substrate flow rates on DAG production in PBR. Quadratic models were successfully developed for both DAG and unhydrolyzed triacylglycerol (TAG) with insignificant lack of fit (P>0.05). Optimum conditions for DAG synthesis were evaluated to be 10 cm packed bed height and 3.8 ml/min flow rate with 29-wt% DAG being reported. Immobilized enzyme can be reused up to 10 times without significant loss in enzymatic activity. The present study also investigated the production efficiency using columns with different length-to-diameter ratios (L/D ratio) to determine the most potential process setup for industrial DAG manufacturing. Practical design issues such as operating temperature, substrate flow rate and reaction time were evaluated with respect to various packed bed column configurations. A column dimension with L/D ratio of two was determined to be the most suitable bed column design for lipase-mediated partial hydrolysis reaction. The optimal reaction temperature, substrate flow rate and residence time for the production of DAG in packed bed column dimension of two were found to be 55oC, 5 ml/min and 5.8 min, respectively. Under these operating conditions, a maximal DAG content of 35- wt% was obtained within the first 2 h. Since scientific knowledge is lacking in the employment of PBR for the production of DAG-enriched oil via enzyme-catalysed partial hydrolysis, the findings of the study would facilitate the design of a pilotscale fixed bed reactor system for lipase-mediated partial hydrolysis to obtain DAG-enriched oil as functional oil without constraints.